Desmin Knock-Out Cardiomyopathy: A Heart on the Verge of Metabolic Crisis - Elsnicova, Barbara; Hornikova, Daniela; Tibenska, Veronika; Kolar, David; Tlapakova, Tereza; Schmid, Benjamin; Mallek, Markus; Eggers, Britta; Schlötzer-Schrehardt, Ursula; Peeva, Viktoriya; Berwanger, Carolin; Eberhard, Bettina; et al. (International Journal of Molecular Sciences, 2022)
Desmin mutations cause familial and sporadic cardiomyopathies. In addition to perturbing the contractile apparatus, both desmin deficiency and mutated desmin negatively impact mitochondria. Impaired myocardial metabolism secondary to mitochondrial defects could conceivably exacerbate cardiac contractile dysfunction. We performed metabolic myocardial phenotyping in left ventricular cardiac muscle tissue in desmin knock-out mice. Our analyses revealed decreased mitochondrial number, ultrastructural mitochondrial defects, and impaired mitochondria-related metabolic pathways including fatty acid transport, activation, and catabolism. Glucose transporter 1 and hexokinase-1 expression and hexokinase activity were increased. While mitochondrial creatine kinase expression was reduced, fetal creatine kinase expression was increased. Proteomic analysis revealed reduced expression of proteins involved in electron transport mainly of complexes I and II, oxidative phosphorylation, citrate cycle, beta-oxidation including auxiliary pathways, amino acid catabolism, and redox reactions and oxidative stress. Thus, desmin deficiency elicits a secondary cardiac mitochondriopathy with severely impaired oxidative phosphorylation and fatty and amino acid metabolism. Increased glucose utilization and fetal creatine kinase upregulation likely portray attempts to maintain myocardial energy supply. It may be prudent to avoid medications worsening mitochondrial function and other metabolic stressors. Therapeutic interventions for mitochondriopathies might also improve the metabolic condition in desmin deficient hearts.
CRIS-Team Scopus Importer:2022-10-28
Keywords: amino acid; cardiomyopathy; creatine kinase; desmin; desmin knock-out metabolism; desminopathy; fatty acid; glucose; mitochondria; mitochondriopathy